2019
DOI: 10.1002/jum.15004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Left Atrial Functions by 2‐dimensional Speckle‐Tracking Echocardiography During Healthy Pregnancy

Abstract: Objectives We aimed to determine the effects of normal pregnancy on left atrial (LA) mechanics using 2‐dimensional speckle‐tracking echocardiography. Methods A total of 47 healthy women with singleton pregnancies were prospectively enrolled in this study. A total of 4 visits, including each trimester and postpartum at 6 months, were planned. Echocardiographic studies were performed with a Vivid 7 device equipped with a 2.5‐MHz transducer (GE Vingmed Ultrasound AS, Horten, Norway). Results Although the LA reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Left atrial strain and strain rate were measured by speckle-tracking echocardiography (STE). We manually traced three markers in the left atrial maximum volume view, acquired the curve of the strain rate and calculated the average value in both the two-chamber and fourchambe viewsr [14]. The images were recorded over three consecutive cardiac cycles with a stable echocardiographic appearance.…”
Section: Echocardiography and Speckle-tracking Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…Left atrial strain and strain rate were measured by speckle-tracking echocardiography (STE). We manually traced three markers in the left atrial maximum volume view, acquired the curve of the strain rate and calculated the average value in both the two-chamber and fourchambe viewsr [14]. The images were recorded over three consecutive cardiac cycles with a stable echocardiographic appearance.…”
Section: Echocardiography and Speckle-tracking Echocardiographymentioning
confidence: 99%
“…Since LBB is a wide network, implanting the lead to the sub-endoucardium of left septum could easily capture left conduction system [12]. And LBBP has been demonstrated its feasibility and efficacy in LBBB cases with heart failure due to this characteristics [13,14]. The purpose of this study was to use brain natriuretic peptide (BNP), echocardiography and speckle-tracking echocardiagraphy to compare the changes in cardiac function (especially left atrial function, and left ventricular diastolic function) within 7 days between LBBP and RVOP in pacemaker-dependent patients.…”
Section: Introductionmentioning
confidence: 99%
“…LA makes a large contribution to LV filling and thus plays an important role in the pathophysiology and progression of cardiovascular disease [5]. Although some studies on maternal LA structure and performance during pregnancy, those reports just focused on the volumetric analysis [16,14] or the adaptive changes during the healthy pregnancy rather than PE pregnant course [14,15]. To the best of our knowledge, this study is the first to demonstrate the LA myocardial deformation and atrial compliance by STE in the patients suffering from PE.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few reports about the effects of PE on maternal LA mechanics though some studies described the STE-derived LA deformation parameters in normal pregnancy and the postpartum period [14,15]. In the previous studies, using a real-time three-dimensional echocardiography, we identified the dilated atrial chamber and reduced volumetric action of LA occurring during the course of PE [16].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the increased venous return, the dimension of the left atrium expands. Recently Tasar et al [7] showed that left atrial area and volume increase whereas left atrial strain decrease from the first trimester to the third trimester during pregnancy. LV diameters increased during pregnancy but did not reach significance.…”
Section: Discussionmentioning
confidence: 99%